Mode III interlaminar fracture of carbon/epoxy laminates using a four-point bending plate test - Morais, A.B. de
A new four-point bending plate (4PBP) test was used for characterising the mode III interlaminar fracture of carbon/epoxy laminates. The specimen has a cross-ply lay-up and two edge delaminations whose propagation becomes visible at the edges. Although the test setup is very simple, determination of the mode III critical strain energy release rate GIIIc requires finite element analyses (FEA). The virtual crack closure technique with an assumed initiation region was first proposed for computing GIIIc. This scheme was subsequently validated by crack growth simulations with a cohesive zone model. The results showed an average GIIIc = 1550 J/m2, which is significantly higher than the GIIIc = 850 to 1100 J/m2 and GIIc = 800 J/m2 measured in previous studies.